Investigation of indoor propagation of WLAN signals - Mohammed Sameer Salim; khalil Hassan Sayidmarie; Abdullah Hassan Aboud (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The propagation of radio waves inside a typical university building is investigated by simulation and measurements. The Line of sight (LOS) and Obstructed Line of sight (OLOS) propagation scenarios were considered. The received power from a WLAN access point operating at 2.45GHz was determined from the simulations and measurements at various positions, orientations, and heights of the Tx and Rx antennas. The path loss exponents were estimated from the obtained simulation and measurement results of the received power variation with distance. The obtained path loss exponent values were found between 1.15-1.63 for LOS propagation and 2.14-2.55 for OLOS.